Arthroscopic partial meniscectomy for a degenerative meniscus tear: a 5 year follow-up of the placebo-surgery controlled FIDELITY (Finnish Degenerative Meniscus Lesion Study) trial. Issue 22 (27th August 2020) - Sihvonen, Raine; Paavola, Mika; Malmivaara, Antti; Itälä, Ari; Joukainen, Antti; Kalske, Juha; Nurmi, Heikki; Kumm, Jaanika; Sillanpää, Niko; Kiekara, Tommi; Turkiewicz, Aleksandra; Toivonen, Pirjo; et al.
Abstract : Objectives: To assess the long-term effects of arthroscopic partial meniscectomy (APM) on the development of radiographic knee osteoarthritis, and on knee symptoms and function, at 5 years follow-up. Design: Multicentre, randomised, participant- and outcome assessor-blinded, placebo-surgery controlled trial. Setting: Orthopaedic departments in five public hospitals in Finland. Participants: 146 adults, mean age 52 years (range 35–65 years), with knee symptoms consistent with degenerative medial meniscus tear verified by MRI scan and arthroscopically, and no clinical signs of knee osteoarthritis were randomised. Interventions: APM or placebo surgery (diagnostic knee arthroscopy). Main outcome measures: We used two indices of radiographic knee osteoarthritis (increase in Kellgren and Lawrence grade ≥1, and increase in Osteoarthritis Research Society International (OARSI) atlas radiographic joint space narrowing and osteophyte sum score, respectively), and three validated patient-relevant measures of knee symptoms and function (Western Ontario Meniscal Evaluation Tool (WOMET), Lysholm, and knee pain after exercise using a numerical rating scale). Results: There was a consistent, slightly greater risk for progression of radiographic knee osteoarthritis in the APM group as compared with the placebo surgery group (adjusted absolute risk difference in increase in Kellgren-Lawrence grade ≥1 of 13%, 95% CI −2% to 28%; adjusted absolute mean difference in OARSI sum score 0.7, 95% CI 0.1 to 1.3). There were no relevant between-group differences in the three patient-reported outcomes: adjusted absolute mean differences (APM vs placebo surgery), −1.7 (95% CI −7.7 to 4.3) in WOMET, −2.1 (95% CI −6.8 to 2.6) in Lysholm knee score, and −0.04 (95% CI −0.81 to 0.72) in knee pain after exercise, respectively. The corresponding adjusted absolute risk difference in the presence of mechanical symptoms was 18% (95% CI 5% to 31%); there were more symptoms reported in the APM group. All other secondary outcomes comparisons were similar. Conclusions: APM was associated with a slightly increased risk of developing radiographic knee osteoarthritis and no concomitant benefit in patient-relevant outcomes, at 5 years after surgery. Trial registration: ClinicalTrials.gov (NCT01052233 and NCT00549172 ).